Implementasi Konsep Matematika pada Metode ‘Aul dalam Pembagian Harta Warisan - Lutfiana, Fira Aini; Nurjanah; Sulastri, Yayu Laila; Fadilawati, Fani; Syakur, Novia Nurwasyi; Nurwahid, Eef Hidayat (Polinomial : Jurnal Pendidikan Matematika, 2025)
The 'Aul method in Islamic inheritance law is used when the total portions assigned to heirs exceed 100%. Mathematics plays a crucial role in ensuring fair and Sharia-compliant distribution. This study, titled "The Implementation of Mathematical Concepts in the 'Aul Method of Inheritance Distribution," explores how mathematics is applied in this method. Using a literature review with interpretative and hermeneutic approaches, data were gathered from relevant sources with the help of data analysis tables and expert validation sheets, then analyzed using content analysis. The study focuses on the practical use of the 'Aul method in inheritance distribution. Findings show that mathematical concepts such as fractions, arithmetic operations, least common multiples (LCM), sets, and ratios are used. This research aims to support mathematics education and provide deeper insight into Islamic studies.